Variability of nutrient transport and associated upper ocean primary production induced by Kuroshio meanders in the Enshu-nada Sea, Japan - Namazue Gaku; Uchiyama Yusuke; Zhang Xu; Masunaga Eiji (E3S Web of Conferences)
Towards the desirable preservation of the marine environment under a changing global climate, this study aims to investigate the coastal biological response to varying oceanic conditions, namely the Kuroshio meander, and associated nitrate transport on the Pacific coast of Japan around the Enshu-nada Sea, using a coupled three-dimensional regional ocean circulation model with a nitrogen-based ecosystem model. A prominent difference was found in nitrate transport processes between for a period when the Kuroshio took a meandering path and for a non-meandering period, leading to about 1.5 times higher surface primary production measured by chlorophyl-a concentration during the non-meandering period than during the meandering period. The upper ocean nitrate flux budget analysis showed that the subsurface nitrate was transported upward as a vertical diffusive flux around the north (shoreward) of the Kuroshio path and as a mean vertical advective flux in the Kuroshio downstream region around the Izu-Ogasawara Ridge. In contrast, high-frequency eddy vertical advective fluxes caused downward transport, but to a degree about 20% smaller than the other fluxes. After nitrate was supplied to the upper layer, it was transported horizontally by the counterclockwise rotating cyclonic eddy formed between the coast and the Kuroshio and supplied to phytoplankton in the Enshu-nada Sea. These results suggest that carbon sequestration due to biological pump may also vary in response to the Kuroshio that is influenced by basin-scale oceanic conditions.